(untitled) (The Pakistan Development Review, 1993)
In the past, studies on poverty in a developing country like Pakistan have usually been based on an absolute (e. g. basic needs) concept of poverty see, e. g., Naseem (1977); Irfan and Amjad (1984); Ercelawn (1990) and Malik (1992). In this paperl we will state the case for using relative poverty thresholds, and present poverty statistics for Pakistan based on data from the Household Income and Expenditure Survey (1987-88). [Government of Pakistan (1988)]. The paper will also show the consequences of different choices in the assessment of the poverty threshold. In particular, instead of using one rather steep equivalence scale, as is the common practice in most studies, we will present poverty statistics based on three different -equivalence scales. The effects of choices with respect to the concept of resources and the measure of poverty, will also be examined. After a discussion of the concept of poverty (Section II), we compare the size and composition of the poor population using three relative poverty lines in Section III. In Section IV we present a number of sensitivity analyses, which show the effects of using different equivalence scales, using different indicators of household resources (income or total expenditures), and using measures of poverty different from the Head-count measure. The poverty incidence differentiated according to household characteristics is further analysed by means of cross-classification and logit analysis in Section V. Section VI presents some general conclusions.